Factors Influencing the Choice of Child Delivery Location among Women Attending Antenatal Care Services and Immunization Clinic in Southeastern Nigeria - Johnbull Egharevba, MD, MPH; Jennifer R Pharr, PhD; Brian van Wyk, PhD; Echezona E Ezeanolue, MD, MPH (Global Health and Education Projects, Inc., 2017)
Background and Objective: In Nigeria, most deliveries take place at home or with traditional birth attendants (TBAs). This study examined the factors that influenced or determined utilization of healthcare facility delivery services among women who attended antenatal care (ANC) services. Methods: A cross-sectional survey was conducted with 220 women who registered for ANC at a hospital and delivered within 18 months. Associations between independent variables and choice of healthcare facility delivery were analyzed. Multiple logistic regression was also used to identify the predictors of choice of delivery among women. Results: Of the 220 women who registered for ANC, 75% delivered at a healthcare facility while 15% delivered with a TBA or at home. In the final model, number of children, having planned to deliver at a hospital, labor occurring at night, and labor allowing time for transportation were significant predictors of child delivery location among the women. Conclusion and Global Health Implications: Utilization of the health facilities for childbirth may increase if pregnant women are encouraged to book early for ANC and if during ANC, pregnant women were counseled to detect labor signs early. In addition to focused and intensified counseling for women with more children, support should be provided that includes financial provisions for transportation to the healthcare facility. Key words: Delivery Location • Pregnant Women • Maternal Utilization • Healthcare Facility Delivery • Skilled Birth Attendants • Traditional Birth Attendants (TBA) • Antenatal Care Services (ANC) • Nigeria Copyright © 2017 Egharevba et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.